Pengaruh Profitabilitas Dan Der Terhadap Return Saham: Studi Empiris Pada Perusahaan Sub Sektor Transportasi Yang Terdaftar Di Bursa Efek Indonesia Periode Tahun 2020-2024 - Eunike Mendrofa; Candra Astra Terenggana; Ega Leovani; Carin Mareta (ATRABIS Jurnal Administrasi Bisnis (e-Journal), 2026)
This study was conducted to examine the effect of profitability, measured by Return on Assets (ROA), and leverage, measured by Debt to Equity Ratio (DER), on stock returns in transportation sub-sector companies listed on the Indonesia Stock Exchange during the 2020–2024 period. The data were analyzed using multiple linear regression with the assistance of IBM SPSS software. The classical assumption tests showed that the residuals were normally distributed, with no indications of multicollinearity, heteroscedasticity, or autocorrelation. The results of the partial test (t-test) indicated that both ROA and DER had no significant effect on stock returns. Furthermore, the simultaneous test (F-test) showed that ROA and DER did not significantly affect stock returns. The coefficient of determination (R²) revealed that the ability of ROA and DER to explain variations in stock returns was very low, indicating that most variations in stock returns were influenced by other factors outside the model. Therefore, profitability (ROA) and leverage (DER) were not determinants of stock returns in transportation sub-sector companies during the research period.